Trade Credit Contracts - Klapper, Leora; Laeven, Luc; Rajan, Raghuram (2012)
The authors employ a novel dataset on almost 30,000 trade credit contracts to describe the broad characteristics of the parties that contract together; the key contractual terms, such as the discount for early payment; and the days by when payment is due. Whereas prior work has typically used information on only one side of the buyer-seller transaction, this paper utilizes information on both. The authors find that the largest and most creditworthy buyers receive contracts with the longest maturities from smaller suppliers, with the latter extending credit to the former perhaps as a way of certifying product quality. Discounts for early payment seem to be offered to riskier buyers to limit the potential nonpayment risk when credit is extended for non-financial reasons.